The Effect of Hope on Academic Persistence Mediated by Learning Engagement in University Students - Binti Mahmud, Siti Nurhaliza; Santoso, Agus; Muñoz, Nayelli (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the effect of hope on academic persistence among university students, with learning engagement as a mediating variable.Methods and Materials: A descriptive correlational research design was employed with a sample of 390 undergraduate students from various universities in Indonesia, selected based on the Morgan and Krejcie sample size determination table. Data were collected using the Adult Dispositional Hope Scale, the Utrecht Work Engagement Scale–Student Version, and the Academic Persistence Scale, all of which have demonstrated established validity and reliability in prior research. Descriptive statistics, Pearson’s correlation analysis, and Structural Equation Modeling (SEM) were conducted. Pearson’s correlation coefficients were computed using SPSS version 27, while SEM analyses were performed using AMOS version 21, with model fit assessed via χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices.Findings: Results indicated significant positive correlations between hope and academic persistence (r = .53, p < .001), hope and learning engagement (r = .61, p < .001), and learning engagement and academic persistence (r = .58, p < .001). The SEM model demonstrated an excellent fit to the data (χ²(84) = 162.47, χ²/df = 1.93, GFI = .95, AGFI = .92, CFI = .97, TLI = .96, RMSEA = .049). Hope had a significant direct effect on academic persistence (β = .34, p < .001) and an indirect effect via learning engagement (β = .20, p < .001). Learning engagement significantly predicted academic persistence (β = .38, p < .001). The total effect of hope on persistence was β = .54, underscoring the mediating role of engagement.Conclusion: These findings highlight the pivotal role of hope in fostering academic persistence, both directly and indirectly through learning engagement, suggesting that interventions targeting these constructs may enhance student retention and success in higher education.